Infectious Complications of Acute and Chronic Liver Disease - Leber, Bettina; Spindelboeck, Walter; Stadlbauer, Vanessa (Seminars in Respiratory and Critical Care Medicine, 2012)
Acute and chronic liver diseases are frequently complicated by infections, which result in increased morbidity and mortality and place an economic burden on health care systems. This review discusses the epidemiology and the impact on prognosis of infections in liver cirrhosis, nonalcoholic fatty liver disease/nonalcoholic steatohepatitis, acute liver failure, and post–liver transplantation. Possible mechanisms for this increased susceptibility are innate immune dysfunction (Kupffer cells, neutrophils, monocytes), genetic predisposition, and intrinsic cellular defects. The causes for innate immune dysfunction may lie in increased gut permeability, the occurrence of endotoxemia, albumin and lipoprotein dysfunction, or toll-like receptor expression. From a clinical viewpoint this article discusses problems in diagnosing infection. Established (vaccination, antibiotic prophylaxis, antiviral prophylaxis, and nutrition) and experimental (probiotic) prophylactic strategies as well as established (antibiotics) and experimental (liver support, albumin, toll-like receptor antagonists) strategies are also reviewed.
Keywords: infection; liver cirrhosis; acute liver failure; immune dysfunction